PRINSIP MORAL PADA PENGATURAN PERIKATAN ALAM - Purwadi, Ari (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2020)
Abstract Natural obligations is not a civil obligations, so that the legal consequences cannot be prosecuted legally. The legal consequences of natural obligations are a test of the moral principles of law. The scope of natural obligations occurrence can occurs because regulated by positive law or because of decency and advisability. Occurrence of natural obligations arrangement by positive law is a manifestation of legal certainty principles, giving rise to a relationship between laws and morals. While the occurrence of natural obligations because decency and advisability is a manifestation of justice principles, so that the application by the judge refers to moral under using law finding methods.Keywords: law; moral; natural obligationsAbstrak Perikatan alam bukanlah perikatan perdata, sehingga menimbulkan akibat hukum tidak dapat dilakukan penuntutan secara hukum. Akibat hukum pada perikatan alam itu merupakan pengujian prinsip moral terhadap hukum. Ruang lingkup terjadinya perikatan alam dapat terjadi karena adanya pengaturan oleh hukum positif atau karena kepatutan dan kelayakan. Pengaturan terjadinya perikatan alam oleh hukum positif merupakan wujud adanya prinsip kepastian hukum, sehingga menimbulkan hubungan antara hukum dan moral. Sedangkan terjadinya perikatan alam karena kepatutan dan kelayakan merupakan wujud adanya prinsip keadilan, sehingga dalam penerapan oleh hakim mengacu pada moral dengan menggunakan metode penemuan hukum.Kata kunci: hukum; moral; perikatan alam